A record of the Jurassic massive plate shift from the Garedu Formation of central Iran - M. Mattei; F. Cifelli; G. Muttoni (Geology, 2014)
Modern generations of apparent polar wander paths (APWPs) show the occurrence in North American and African coordinates of a major and rapid shift in pole position (plate shift) during the Middle to Late Jurassic (175-145 Ma) that alternative curves from the literature tend to underestimate. This Jurassic massive polar shift (JMPS), of vast and as-yet unexplored paleogeographic implications, is also predicted for Eurasia from the North Atlantic plate circuit, but Jurassic data from this continent are scanty and problematic. Here we present paleomagnetic data from the Kimmeridgian-Tithonian (upper Jurassic) Garedu Formation of Iran, which was part of Eurasia since the Triassic. Paleomagnetic component directions of primary (pre-folding) age indicate a paleolatitude of deposition that is in excellent agreement with the latitude drop predicted for Iran from APWPs incorporating the JMPS. Moreover, we show that paleolatitudes calculated from these APWPs, used in conjunction with simple zonal climate belts, better explain the overall stratigraphic evolution of Iran during the Mesozoic. As Iran drifted from the tropical arid belt to the mid-latitude humid belt in the Late Triassic, carbonate platform productivity stopped while widespread coal-bearing sedimentation started, whereas as Iran returned to arid tropical latitudes during the JMPS, carbonate platform productivity and evaporitic sedimentation resumed. These results illustrate (1) the potent, but often neglected, control that plate motion (continental drift and/or true polar wander) across zonal climate belts exerts on the genesis of sedimentary facies; and (2) the importance of precisely controlled paleogeographic reconstructions for tectonic interpretations, especially during times of fast plate motion like the Jurassic. As a suggestion for future research, we predict that the adoption of Eurasian reference paleopoles incorporating the JMPS may lead to a reconciliation (or reinterpretation) of existing geologic and paleomagnetic data regarding the deformation ...